Transcriptome, Proteome, Histology, and Biochemistry Analysis of Oriental River Prawn Macrobrachium nipponense under Long-term Salinity Exposure - Yaoran Fan; Xiao Wu; Feiyue Ling; Zefei Wang; Keyi Ma; Nan Xie; Juanying Li; Jianbin Feng; Jiale Li (Frontiers in Marine Science, 2023)
Salinity is an ecological factor affecting the physiology, survival, and distribution of crustaceans. Additionally, salinity fluctuation detrimentally affects the composition and biological process of crustaceans. As a significant commercial aquaculture species in China, Japan, and Southeast Asian countries, the oriental river prawn, Macrobrachium nipponense, can tolerate a wide range of salinity. The transcriptome, proteome, histology, and physiology analysis were utilized to explore the physiological responses and molecular mechanisms of salinity tolerance in M. nipponense . Through the three-month culture, the statistic of growth trait illustrated the relatively excellent performance of M. nipponense in low salinity, and the higher salinity exposure significantly affected the growth of M. nipponense . In terms of the histological analysis, the gills and hepatopancreas of M. nipponense suffered varying degrees of damage. Besides, the activities of the digestive, immune-related, and metabolic enzymes were calculated. These results indicated that salinity significantly influenced trypsin and amylase in hepatopancreas, especially in 14 ppt. The immune-related enzymes were activated in high salinity. Notably, the activity of metabolic enzymes was significantly low in 7 and 14 ppt, which testified that the 7 ppt to 14 ppt were near the isotonic point of M. nipponense . In gills, hepatopancreas, and muscle, high-throughput mRNA sequencing revealed 11356, 2227, and 1819 differentially expressed genes (DEGs) by comparing the 7, 14, and 21 ppt groups with the 0ppt group, respectively. The TMT-labeling proteome identified 439 and 230 differentially expressed proteins (DEPs) in gills and hepatopancreas through the comparison of the 7, 14, and 21 ppt groups to the 0 ppt group, respectively. Additionally, through the integration of transcriptome and proteome, several pathways related to salinity adaptation were enriched, including protein export, cGMP-PKG signaling pathway, Amino sugar and nucleotide sugar metabolism, and Glycine, serine and threonine metabolism. Besides, 16 up and down-regulated proteins and related DEGs were detected through KEGG enrichment analysis, including ETHE1, BIP, chitinase (E3.2.1.14), and SARDH. Notably, no significantly regulated proteins and related DEGs were recorded by the correlation of transcriptome and proteome of 0 ppt and 7 ppt in hepatopancreas. Thus, the optimum survival salinity of M. nipponense may range from 0 ppt to 7 ppt. Overall, these results may provide valuable insights into the mechanisms underlying the culture of M. nipponense in different salinity.